2015
DOI: 10.1038/ncomms6905
|View full text |Cite
|
Sign up to set email alerts
|

An invisible acoustic sensor based on parity-time symmetry

Abstract: Sensing an incoming signal is typically associated with absorbing a portion of its energy, inherently perturbing the measurement and creating reflections and shadows. Here, in contrast, we demonstrate a non-invasive, shadow-free, invisible sensor for airborne sound waves at audible frequencies, which fully absorbs the impinging signal, without at the same time perturbing its own measurement or creating a shadow. This unique sensing device is based on the unusual scattering properties of a parity-time (PT) symm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
435
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 679 publications
(444 citation statements)
references
References 43 publications
8
435
0
1
Order By: Relevance
“…However, this technique is only valid for a single physical fi eld, e.g., an invisible electromagnetic sensor or an invisible acoustic detector. [2][3][4] Consequently, a single-functional sensor is invisible to an acoustic monitoring receiver, but it can be easily detected using a remote thermal imager. Is it possible to create a sensor that is invisible in multiple physical fi elds while maintaining the same sensing functionality?…”
Section: Doi: 101002/adma201502513mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique is only valid for a single physical fi eld, e.g., an invisible electromagnetic sensor or an invisible acoustic detector. [2][3][4] Consequently, a single-functional sensor is invisible to an acoustic monitoring receiver, but it can be easily detected using a remote thermal imager. Is it possible to create a sensor that is invisible in multiple physical fi elds while maintaining the same sensing functionality?…”
Section: Doi: 101002/adma201502513mentioning
confidence: 99%
“…This is a more advanced technique because previous "cloaking a sensor" techniques were only valid in a single physical fi eld. [1][2][3][4] To this day, no theoretical or experimental works have been proposed that cloak or camoufl age a sensor in a multiphysical environment. We believe this is a step toward cloaking a sensor in a realistic environment, without it being detected by different types of remote observers.…”
Section: Doi: 101002/adma201502513mentioning
confidence: 99%
“…Based on unidirectional invisibility in acoustics, a noninvasive, shadow-free, fully invisible acoustic sensor with PT symmetry was recently demonstrated [140]. Unidirectional invisibility at EPs in optics may also have remarkable implications for noninvasive sensing.…”
Section: Discussionmentioning
confidence: 99%
“…This largely originates from the work of Bender [9,10], who showed that operators with real spectra are not necessarily Hermitian. PT-symmetric potentials have since been translated into optics and acoustics where it has been realised that such potentials can be perfectly transparent for waves incident from one side [11][12][13][14][15][16], 2 an effect that has been confirmed in recent experiments [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%